Real-world Outcomes of Relapsed/Refractory Diffuse Large B-cell Lymphoma Treated With Polatuzumab Vedotin-based Therapy. Issue 12 (11th December 2022) - Argnani, Lisa; Broccoli, Alessandro; Pellegrini, Cinzia; Fabbri, Alberto; Puccini, Benedetta; Bruna, Riccardo; Tisi, Maria Chiara; Masia, Francesco; Flenghi, Leonardo; Nizzoli, Maria Elena; Musso, Maurizio; Salerno, Marilena; et al.
Abstract : After FDA and EMA approval of the regimen containing polatuzumab vedotin plus rituximab and bendamustine (PolaBR), eligible relapsed/refractory diffuse large B-cell lymphoma (DLBCL) patients in Italy were granted early access through a Named Patient Program. A multicentric observational retrospective study was conducted focusing on the effectiveness and safety of PolaBR in everyday clinical practice. Fifty-five patients were enrolled. There were 26 females (47.3%), 32 patients were primary refractory and 45 (81.8%) resulted refractory to their last therapy. The decision to add or not bendamustine was at physician's discretion. Thirty-six patients underwent PolaBR, and 19 PolaR. The 2 groups did not differ in most of baseline characteristics. The final overall response rate was 32.7% (18.2% complete response rate), with a best response rate of 49.1%. Median disease-free survival was reached at 12 months, median progression-free survival at 4.9 months and median overall survival at 9 months, respectively. Overall, 88 adverse events (AEs) were registered during treatment in 31 patients, 22 of grade ≥3. Eight cases of neuropathy occurred, all of grades 1–2 and all related to polatuzumab. The two groups of treatment did not differ for effectiveness endpoints but presented statistically significant difference in AEs occurrence, especially in hematological AEs, in AEs of grade equal or greater than 3 and in incidence of neuropathy. Our data add useful information on the effectiveness of Pola(B)R in the setting of heavily pretreated DLBCL and may also suggest a better tolerability in absence of bendamustine without compromise of efficacy.